THE EFFECTIVENESS OF USING PEER ASSESSMENT TECHNIQUE IN TEACHING SPEAKING AT FIRST GRADE OF MAN 4 KEDIRI - Rahendra, Judith Aditya; Asyhar, Wildan Isna (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2021)
Peer assessment is an innovation in the field of assessment which aims to improve the quality of learning. Peer assessment is one approach to obtain information that might help determine the value of the individual. This research was intended to know the effectiveness of using Peer Assessment in teaching speaking at first grade of MAN 4 Kediri. This research used a quantitative approach, while the design used was the posttest-only control group design. In this research used two classes, there is an experimental group and control group. The experimental group used the peer assessment method, and the control group was taught using the conventional method. To collect the data, post speaking tests in the experimental and control groups were administered. Data were analyzed using mean scores, standard deviation, and independent-sample t-test. The result of this research showed that the t-test was higher than t – table with a degree of freedom. It can be concluded that using peer assessment in teaching speaking is effective.